2017
DOI: 10.1155/2017/1567467
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Composition of Major Fatty Acids and Fat Distribution and Insulin Resistance in Japanese

Abstract: Objective. The aim of this study was to evaluate the relationships between the composition of free fatty acids (FFAs) and metabolic parameters, including body fat distribution, in Japanese. Methods. The study subjects were 111 Japanese patients (54 males, 57 females). Metabolic parameters and visceral and subcutaneous fat areas as determined by CT scanning at the umbilical level were measured. Glucose tolerance test (GTT) was performed by administering 75 g glucose orally. Results. The percentage of linoleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Insulin resistance does not always involve the high concentration of blood glucose according to the results by Fujii et al [18], Samant et al [26], and Yin et al [42]. The results reported by Fujii et al [18] and Samant et al [26] suggested that patients with possible insulin resistance defined by HOMA-IR ≥ 2.5 [19] were not in the condition of high blood glucose, but the patients with diabetes were in the condition of high blood glucose [18].…”
Section: Relation Between Insulin Resistance and Blood Glucose Levelsmentioning
confidence: 96%
See 4 more Smart Citations
“…Insulin resistance does not always involve the high concentration of blood glucose according to the results by Fujii et al [18], Samant et al [26], and Yin et al [42]. The results reported by Fujii et al [18] and Samant et al [26] suggested that patients with possible insulin resistance defined by HOMA-IR ≥ 2.5 [19] were not in the condition of high blood glucose, but the patients with diabetes were in the condition of high blood glucose [18].…”
Section: Relation Between Insulin Resistance and Blood Glucose Levelsmentioning
confidence: 96%
“…Tabák et al showed the changes in glucose concentrations, insulin sensitivity, and insulin secretion as much as 3 -6 years before diagnosis of diabetes [20]. The IGT subjects with mean FG 109.4 ± 1.5 mg/dL reported by Fujii et al [18] seem to be destined to diabetes in a few years based on the graph for FG trajectory before diagnosis of diabetes by Tabák et al [20]. These results suggest that it generally takes several years to migrate from NGT to IGT, and IGT to diabetes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations